Chikungunya, caracterización clínica y diagnóstico de laboratorio - Katherine Briggith, Caiza Cuello (2022)
ABSTRACT This research project fulfilled the objective of collecting information on Chikungunya, clinical characterization, and laboratory diagnosis through the search and analysis of scientific literature. The methodology used was descriptive, documentary design, crosssectional cohort, and retrospective. For the study population, valid information was collected from 96 documents located in the different databases recognized worldwide such as Scielo, Redalyc, ProQuest, Academic Google, Medigraphic, PubMed, as well as from entity websites, for example, from the Pan American Health Organization, World Health Organization and the Ministry of Public Health of Ecuador. From this number, a sample of 71 publications was obtained. The data collection technique was the observation, and guides were used with books and magazines that met the inclusion criteria. The results obtained showed varied symptoms, presenting by acute, subacute, and chronic phases. It depends on the days after infection, with arthralgia, fever, and myalgias being the most representative, although other patients developed different signs and symptoms such as rash, edema, pain retro-orbital, gastrointestinal discomfort, and fatigue. Furthermore, the atypical manifestations in neonates and infants were bullous lesions that led to blisters. Within the laboratory findings, lymphopenia was considered a differential indicator of Dengue. However, confirmatory tests are serological tests for detecting antibodies or molecular tests for the detection of viral ribonucleic acid. Keywords: Chikungunya virus, Aedes, arthralgia, fever, diagnosis. Reviewed by: Mgs. Mario Salazar ENGLISH PORFESSOR C.C 0604069781